2010
DOI: 10.1177/1756287210370330
|View full text |Cite
|
Sign up to set email alerts
|

Current approach to the treatment of penile implant infections

Abstract: Modern penile implants, introduced to the market almost four decades ago, have provided a predictable and reliable treatment of erectile dysfunction (ED) despite the development of less-invasive therapies. Infection associated with the placement of these devices does occur, and with prophylactic measures and protocols the incidence has decreased fortunately. In the presence of an infection the implant and all foreign material should be removed. A salvage procedure, during which the wound is thoroughly washed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 39 publications
(39 reference statements)
0
38
0
Order By: Relevance
“…In the absence of clear evidence of PP infection (eg, purulent drainage, significant and increasing edema), a trial of oral antimicrobials such as bactrim or ciprofloxacin can be attempted. 6 This trial may also be diagnostic, because the symptoms persistently improve in cases of superficial skin infection, whereas the recurrence of symptoms after stopping the antibiotics is consistent with an actual PP infection requiring explantation.…”
Section: Infections Of Penile Prosthesesmentioning
confidence: 95%
See 2 more Smart Citations
“…In the absence of clear evidence of PP infection (eg, purulent drainage, significant and increasing edema), a trial of oral antimicrobials such as bactrim or ciprofloxacin can be attempted. 6 This trial may also be diagnostic, because the symptoms persistently improve in cases of superficial skin infection, whereas the recurrence of symptoms after stopping the antibiotics is consistent with an actual PP infection requiring explantation.…”
Section: Infections Of Penile Prosthesesmentioning
confidence: 95%
“…However, in the past decade, the understanding of the mechanisms and causes of infection has increased, which has led to markedly decreased infection rates. 6 At present, the most commonly implanted device for ED treatment is the inflatable PP, a 3-piece device consisting of 2 corporal cylinders, a pump, and a separate reservoir. 4 An alternative for patients is the semirigid (malleable) prosthesis or a 2-piece PP.…”
Section: Infections Of Penile Prosthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several physical and psychological components are involved in erectile function, including hormonal, neurological, vascular and cavernous body diseases 2,3 . Studies have demonstrated a high prevalence of ED in men with cardiovascular diseases, since both diseases have several risk factors in common 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of diabetes, urinary tract infections, blood coagulation disorders, immune depression, duration of hospitalisation, inappropriate surgical technique and prolonged surgery time should all be assessed (19).A psychological assessment is also important, to understand if the patient is aware not only of the benefits of a penile implant but also of its impact on his personal and relational life (use of loose clothing, practice of nudism, swimming, sports and gym activities, cycling or competitive motorcycling, medical follow-up and examinations).Prosthetic infections are a complex problem. If not immediately resolved on initial antibiotic treatment, removal of the infected implant is considered mandatory.…”
Section: Introductionmentioning
confidence: 99%